Instagram Content Impact on Digital Literacy Capability - Dedeh Fardiah; Ferry Darmawan; Rini Rinawati; Yuristia Wira Cholifah; Sandi Ibrahim Abdullah (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2023)
Instagram has become a social media with many users. Previous research has shown that Instagram content is often associated with learning media, promotion, entertainment, and politics. The purpose of this study is to see the relationship between Instagram content and people's digital literacy skills. Using the correlational method, the survey respondents were followers of the @jabarsaberhoaks Instagram account, which reached 59.5 thousand. The results showed two main content elements of @jabarsaberhoaks visual aspects of photos and videos, as well as textual elements that accompanied the visuals. While the themes raised consist of seven themes, namely saberinfo, saberliteration, saberbudaya, saberquote, sabertainment, saberquiz, and sabermoment. The conclusion of this study is that hoax educational content on Instagram @jabarsaberhoaks has an impact on people's digital literacy levels.